STATUS AND PROBLEMS OF DEVELOPING EDUCATIONAL RESOURCES IN CHINESE LANGUAGE IN HIGHER SCHOOL - T. L. Guruleva (Высшее образование в России)
The article addresses the problems of educational resources development in the Chinese language in higher education. The author gives an analysis of educational resources on the Chinese language, explores the main achievements and the problems connected with the development of educational resources, presents the review of new educational literature in the field of teaching the Chinese language, defines priority areas of the further development of educational resources in the Chinese language in higher education. In the conclusion the author substantiates the need to use the principle of the level-based formation of the communicative competence in the Chinese language. The implementation of this principle will help solve a number of problems in the development of educational resources in the Chinese language, such as: level setting of the goals, stages, content of training and learning outcomes in the Chinese language professional education training program, development of professional competencies based on the communicative competence in the Chinese language, ensuring the continuity of school and university education in the Chinese language, etc.